2018
DOI: 10.1002/brb3.1132
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation therapy for motor recovery in Parkinson's disease: A Meta‐analysis

Abstract: IntroductionTherapeutic effects of repetitive transcranial magnetic stimulation (rTMS) on motor recovery of Parkinson's disease (PD) have been reported; however, the protocols of these studies varied greatly. The aim of this meta‐analysis was to evaluate the optimal rTMS parameters for motor recovery of PD.MethodsElectronic databases were searched for studies investigating the therapeutic effects of rTMS on motor function in patients with PD. The section III of the Unified Parkinson's Disease Rating Scale (UPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 62 publications
(219 reference statements)
8
56
0
Order By: Relevance
“…In summary, the slower activity found in PD patients with motor impairment suggests that these patients could be benefit with excitatory NIBS over frontal and central cortical areas. Several studies have demonstrated that excitatory NIBS has beneficial effect for the treatment of motor symptoms in patients with PD [9][10][11]52]. Though the mechanisms underlying these effects are unclear, the excitatory NIBS seems to be able to reverse the "slowing down" of cortical waves.…”
Section: Insights For Nibs Treatment Based On Cortical Biomarkers In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the slower activity found in PD patients with motor impairment suggests that these patients could be benefit with excitatory NIBS over frontal and central cortical areas. Several studies have demonstrated that excitatory NIBS has beneficial effect for the treatment of motor symptoms in patients with PD [9][10][11]52]. Though the mechanisms underlying these effects are unclear, the excitatory NIBS seems to be able to reverse the "slowing down" of cortical waves.…”
Section: Insights For Nibs Treatment Based On Cortical Biomarkers In Pdmentioning
confidence: 99%
“…Individualized treatment guided by biomarkers certainly will play a crucial role in the more effective treatment of various neurological diseases in the near future [1]. By identifying the biomarkers in the brain of patients with PD may help, for example, in the decision-making process of health professionals regarding the non-invasive brain stimulation (NIBS) treatment, a useful and safe approach to sensorimotor rehabilitation for patients with PD [9][10][11]. Indeed, NIBS treatment seems to modulate qEEG abnormalities in other neurodegenerative disease [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis also suggested that multiple sessions and higher total number of stimulation pulses are associated with higher effect size for long‐term UPDRS III scores . For rTMS frequency, one meta‐analysis suggested that multiple sessions of high‐frequency, bilateral M1 rTMS provided greater benefit than single‐session, low‐frequency, or unilateral M1 rTMS …”
Section: Noninvasive Brain Stimulation In Pdmentioning
confidence: 99%
“…III. Recovery: rTMS has a positive impact on functional recovery, such as limb motor recovery in stroke patients; however, optimal rTMS parameters and high-quality evidence require further research (Pollock et al, 2014;Boonzaier et al, 2018;Yang et al, 2018;Xiang et al, 2019). IV.…”
Section: Abstract As Indicators Of Emerging Trendsmentioning
confidence: 99%